8b-ab=7a, .subtracted from 3a-9ab+b
1 answer:
Answer: You can't. Read explanation.
Step-by-step explanation:
You can't subtract an expression from an equation. If you said something like subtract 8b-ab+7a from 3a-9ab+b that would work, but not here.
Let's just assume You mean it as 8b-ab-7a, then (3a-9ab+b)-(8b-ab-7a) = -8ab + 10a - 7b.
Hope that helped,
-sirswagger21
You might be interested in
Answer:
<h2>0</h2>
Step-by-step explanation:
![30x = 30 - 30](https://tex.z-dn.net/?f=30x%20%3D%2030%20-%2030)
![= > 30x = 0](https://tex.z-dn.net/?f=%20%3D%20%20%3E%2030x%20%3D%200)
![= > x = \frac{0}{30}](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20x%20%3D%20%20%5Cfrac%7B0%7D%7B30%7D%20)
![= > x = 0](https://tex.z-dn.net/?f=%20%3D%20%20%3E%20x%20%3D%200)
Answer:
113
Step-by-step explanation:
supplementray means 180-67=113
Divide the amount of the tax by the cost of the item:
32.80 / 410 = 0.08
Multiply by 100:
0.08 x 100 = 8%
Answer: 8%
The answer is d or b it’s bin along time sense I’ve done it
Answer:
100.
Step-by-step explanation:
By proportion the number of apples sold is (6/4) * 40
= 6 *10
= 60.
Total fruit = 40 + 60 = 100.